Agglomeration and the product mix - Wilfried Dalvai (Universität Rostock, Institut für Volkswirtschaftslehre, 2016)
Worldwide trade flows are dominated by high-productivity firms, that have a large range of products. Since the product range of firms reflects partly trade flows, it is a source of economic differences in space. In this paper, I analyze the effects of the product mix of firms on agglomeration. I build a theoretical model of multiproduct firms à la Mayer, Melitz, and Ottaviano (2014, AER), expand it with skilled, mobile workers and a spatial equilibrium. I show that a larger product mix of firms in a region favours dispersion. The product mix influences the indirect utility through two channels, the wage and consumer surplus. A larger product mix decreases the wage differential between the two regions through a more competitive environment and thus strengthening the dispersion force. More competition means less profits and therefore a lower wage for skilled workers. On the other hand a more competitive environment means a higher consumer surplus which diminishes agglomeration forces.
Keywords: L11; F12; R11; R12; 330; Agglomeration; Heterogenous Firms; Product Mix; Migration